2016
DOI: 10.1159/000448586
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Granulocyte Count Measuring Is Useful for Detecting Asymptomatic Agranulocytosis in Antithyroid Drug-Treated Patients with Graves' Disease

Abstract: Objective: Finding agranulocytosis (AG) at an early stage is important to improve outcome, but periodic granulocyte count monitoring is not generally recommended for patients with Graves' disease, because AG develops suddenly. Method: At the Kuma Hospital, Graves' patients under antithyroid drug (ATD) treatment in an outpatient clinic have a granulocyte count examination during each visit, and if it is <1,000/μl, a warning is immediately sent to the patient's physician. We evaluated the usefulness of this syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…The medical literature recommends monitoring the neutrophil count when certain drugs, such as clozapine, ticlopidine and ATDs, are prescribed [14,25]. The results of the present study seem to support this recommendation.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The medical literature recommends monitoring the neutrophil count when certain drugs, such as clozapine, ticlopidine and ATDs, are prescribed [14,25]. The results of the present study seem to support this recommendation.…”
Section: Discussionsupporting
confidence: 75%
“…In this setting, ATD-induced neutropenia may often be asymptomatic [2,13]. This Grade 1 neutropenia discovery is linked to the routine follow-up of a patient under antithyroid treatment as recommended by several authors and endocrinology societies [2,14]. In this setting, life-threatening manifestations have been reported in more than 2/3 of the cases [11,12,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as Tajiri et al [ 12 ] reported, this is the best method to diagnose asymptomatic patients. A standardized approach with granulocyte count examination at each visit was shown to correctly diagnose 64 and 94% of patients with agranulocytosis or granulocytopenia, respectively, with no or minimum infection symptoms [ 33 ]. On balance, one should try to avoid the most severe and yet unpredictable outcome and thus continue with routine measurements.…”
Section: Preventionmentioning
confidence: 99%